PKM Kewirausahaan Lumpia Aplous - Ratnah S; Nahriana Nahriana; Nur Arisah; Nurjannah Nurjannah; Mustari Mustari (Lembaga Pengembangan Kinerja Dosen, 2024)
Lumpia is a type of food that is very popular in Asia, especially in Indonesia and the Philippines. This food consists of a thin skin filled with various ingredients, such as vegetables, meat, or sweet ingredients. The history of spring rolls can be traced back to Chinese cultural influence in Southeast Asia, where spring rolls were known as